Mortality risk of carbapenem-resistant hypervirulent Klebsiella pneumoniae vs. classical CR-KP: a systematic review and meta-analysis - Chen, Jialiang; Hou, Yue; Shi, Jingang; Gao, Xiaoyi; Liang, Guowei (Frontiers in Public Health, 2025)
BackgroundCarbapenem-resistant Klebsiella pneumoniae (K. pneumoniae, CR-KP) and hypervirulent K. pneumoniae (hvKP) represent two major clinical threats, due to high antimicrobial resistance and enhanced pathogenicity, respectively. The emergence of carbapenem-resistant hypervirulent K. pneumoniae (CR-hvKP) strains, which combine both traits, has raised concerns about increased mortality risk and public health impact. However, existing evidence on clinical outcomes remains fragmented and inconclusive. To systematically compare the mortality risk between CR-hvKP and classical CR-KP (CR-cKP) infections and to explore the impact of hypervirulence definitions, mortality endpoints, infection types, and clinical settings through subgroup analyses.MethodsWe conducted a comprehensive literature search in PubMed, Scopus, Web of Science, and EMBASE up to July 1, 2025. Studies reporting mortality outcomes in patients infected with CR-hvKP and CR-cKP were included. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using a random-effects model. Subgroup analyses were performed to investigate heterogeneity. Sensitivity analysis and Egger’s regression test were used to assess robustness and publication bias.ResultsTen studies with a total of 770 patients (224 with CR-hvKP, 546 with CR-cKP) were included, reporting 315 deaths. The pooled OR for mortality associated with CR-hvKP infection was 2.05 (95% CI: 0.89–4.75), indicating a non-significant trend toward higher mortality. Subgroup analyses indicated significantly increased mortality in studies using phenotypic string tests to define hypervirulence (OR = 4.16), but not in those using genotypic definitions (OR = 1.05). Higher mortality trends were also observed for in-hospital mortality, bloodstream infections, and ICU settings.ConclusionCR-hvKP may be associated with higher mortality risk compared to CR-cKP. The heterogeneity in hypervirulence definitions significantly influences outcome estimates, highlighting the urgent need for standardized diagnostic criteria. These findings underscore the importance of ongoing molecular surveillance, early identification strategies, and targeted infection control measures to mitigate the public health threat posed by CR-hvKP.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251117975, identifier CRD420251117975.